Analisis Kinerja Keuangan PT Unilever Indonesia Tbk Sebelum dan Selama Adanya Aksi Boikot Produk - Syafira; Jamaluddin; Sugianto (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
This study aims to analyze the financial performance of PT Unilever Indonesia Tbk and to see significant differences in its financial performance before and during the product boycott. Financial performance is measured by four ratio indicators, namely liquidity ratio (Current ratio & Quick Ratio), solvency ratio (debt to asset ratio & Debt to Equity Ratio), Profitability Ratio (Return on Asset & Net Profit Margin) and Activity ratio (Total Asset Turnover & Inventory Turnover). The data used in this study are secondary data, in the form of the company's quarterly financial reports for the 2021-2024 period obtained from the company's official website. The data collection technique used is documentation. The data analysis technique used is quantitative descriptive analysis with Saphiro wilk normality test data analysis and Paired Sample T-test. The results show that of the four ratio measurements before and during the product boycott, only the debt to equity ratio solvency ratio is included in the “good” criteria. While for the difference test conducted shows the current ratio liquidity ratio there is a significant difference while the quick ratio shows no difference. solvency ratio shows there is a significant difference before and during the boycott. The profitability ratio also shows a significant difference, while the activity ratio shows no significant difference before and during the boycott.